2017
DOI: 10.1155/2017/1279052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Tongue Indices between Patients with and without a Self‐Reported Yin Deficiency: A Cross‐Sectional Study

Abstract: We investigated the hypothesis that Yin-deficient patients have a reddened tongue with less coating. We screened 189 participants aged 20 to 49 years, complaining of headache. To classify patients in terms of Yin deficiency, we used two self-reporting Yin-deficiency questionnaires (Yin-Deficiency Questionnaire and Yin-Deficiency Scale) and diagnosis by a doctor. Based on the tests, a total of 33 subjects were assigned to a Yin-deficient group and 33 subjects were assigned to a nondeficient control group. Tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…We also noticed that this increase in tongue coating was more prominent on the posterior tongue. Since a small amount of coating is one of the main diagnostic features of the HYD pattern (19), it is conceivable that CBD can ameliorate the adverse impacts of HYD in insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also noticed that this increase in tongue coating was more prominent on the posterior tongue. Since a small amount of coating is one of the main diagnostic features of the HYD pattern (19), it is conceivable that CBD can ameliorate the adverse impacts of HYD in insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PSQI, Veillonella also showed a positive correlation with CIE-a* and diastolic BP in the present study. Since, CIE-a* indicates redness of the tongue body and yin-de cient patients are more likely to have a reddish tongue (19), it is conceivable that Veillonella is an indicator of insomnia, particularly in the presence of a yin-de cient pattern. In addition to the dominant oral microbial genera mentioned above, Peptococcus, Fusobacterium, and Porphyromonas all showed negative correlations with PSQI, Peptococcus and Fusobacterium demonstrated a negative correlation with WMT, and Porphyromonas exhibited negative and positive correlations with PR and TST, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another syndrome classification-based work, conducted by Zhao et al, 85 focused on searching for its correlation with viral hepatitis. Kim et al 58 utilized statistical analysis to prove that the self-reported Yin deficient patients may have more redness in tongue and less tongue coating in comparison to non-Yin-deficient control group. Statistical analysis was further utilized to determine the relationship between ischemic stroke with and without retroflex tongue among 308 patients 86 .…”
Section: Disease Classificationmentioning
confidence: 99%
“…In particular, the tongue coating thickness (TCT) is considered an important indicator of physiological and pathological conditions of qi. [2,3] Moreover, assessment of TCT is used in the field of dentistry, because tongue coating is not only a cause of halitosis but also a risk factor for aspiration pneumonia in edentate elderly individuals. [4]…”
Section: Introductionmentioning
confidence: 99%